A CAMPANHA DO GEN: V. COMO FUNCIONAM OS CROMOSSÔMIOS NA GENÉTICA SEM GENS - Piza Jr., S. de Toledo (REVISTA DE AGRICULTURA, 2015)
A CAMPANHA DO GEN: V. COMO FUNCIONAM OS CROMOSSÔMIOS NA GENÉTICA SEM GENS